Uji Aktivitas Antiinflamasi Ekstrak Etil Asetat Daun Tumbuhan Akar Kaik-Kaik (Uncaria cordata (Lour.) Merr) pada Tikus Putih (Rattus norvegicus) Jantan - Noveri Rahmawati; Gulyla Hari, Dewi; Nurbaiti; Rahmawati, Ayu; Nursyafni; Indriani, Lusi; Lovena, Tri Nova; Arif, Muhammad; Hendri Sandi, Nofri (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2023)
Antiinflammatory activity of ethyl acetate extracts of the leaves of plant Akar Kaik-kaik Uncaria cordata (Lour.) Merr on white male rats. This research examined the quality of crude drugs and extracts ethyl acetate. It is intended to obtain raw materials which can ultimately ensure uniform pharmacologic effect. Antiinflammatory activity of the ethyl acetate extract were tested using the method of paw edema against white male rats. The research were 15 rats mile which divided into 5 groups. Negative control (Na CMC 1%), positive control (Na diklofenak dose 4,5 mg/kgBB) and extract group ethyl acetat with the dose 100, 200 and 400 mg/kgBB given orally. The volume measurement after subcutaneous injection caragen 1% performed with one hour interval for 5 hours assessing with pletysmometer and calculated the inhibition persen. The result of this study showed that the quality of crude drugs and extract ethyl acetate meet the specified requirements Indonesian Herbal Pharmacopoeia. Ethyl acetate extract has significant anti-inflammatory effects to the negative control at doses of 200 and 400 mg/kgBB while against the positive control did not differ significantly white male rats.